2012
DOI: 10.1016/j.jfma.2011.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for candidemia with non-albicans Candida spp. in intensive care unit patients with end-stage renal disease on chronic hemodialysis

Abstract: Central venous catheterization was the only factor significantly associated with BSI due to NAC in ICU patients with end-stage renal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
3
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 29 publications
1
12
3
4
Order By: Relevance
“…Interestingly, Pakshir et al (29) showed C. parapsilosis as the most prevalent Candida species collected from fingernails infection (45.3%), even higher than C. albicans (23.7%). Non-albicans Candida infections may have more incidence among patients with allogeneic hepatocyte transplantation, neutropenia, hematologic malignancies, and severe immune suppression (30,31) however, in our study, there was no difference in neutropenia and malignancies between patients with C. albicans or NAC infections, and diabetes mellitus and pregnancy were the most risk factors.…”
Section: Discussioncontrasting
confidence: 70%
“…Interestingly, Pakshir et al (29) showed C. parapsilosis as the most prevalent Candida species collected from fingernails infection (45.3%), even higher than C. albicans (23.7%). Non-albicans Candida infections may have more incidence among patients with allogeneic hepatocyte transplantation, neutropenia, hematologic malignancies, and severe immune suppression (30,31) however, in our study, there was no difference in neutropenia and malignancies between patients with C. albicans or NAC infections, and diabetes mellitus and pregnancy were the most risk factors.…”
Section: Discussioncontrasting
confidence: 70%
“…Although Candida species in the urine rarely disseminates into the bloodstream, candiduria has a positive association with candidaemia . Prior investigations on the risk factors for candidaemia generally focus on patients in the intensive care units or as a comparison between C albicans vs non‐ albicans species infection . To the best of our knowledge, this is the first study to assess potential patient factors that influence the risk of concurrent candidaemia with candiduria.…”
Section: Discussionmentioning
confidence: 99%
“…In the cohort studies, the observed extrinsic RFs were central venous catheter (CVC) placement, 23,25,[50][51][52][53] ICU admission, [54][55][56][57][58] duration of surgery, 13,17,20,24 steroid use, 13,15,59 previous antibiotic use, 55,60 exposure to cephalosporins before the first episode of infection, 58,61 number of administered antibiotics, 53,62 antimicrobial therapy within 90 days, 63 reoperation, 20,64 transfusion, 50,56,64 invasive mechanical ventilation (IMV), 50,52,65 hospitalization time, 66,67 and a high score on the Acute Physiology and Chronic Health Disease Classification System II. 14,55 Other less frequent extrinsic RFs were found ( Supplementary Table S1).…”
Section: Extrinsic Rfs For Infectionmentioning
confidence: 99%